Enemy Perception and Student Brawling: A case study toward student Brawling at Bogor city Indonesia - Hayadin, Hayadin (KOMUNITAS: International Journal of Indonesian Society and Culture, 2019)
This paper is aiming to explain enemy perception as one factor of the trigger to student brawling. Paper was developed from qualitative research conducted in Bogor city in 2016 until early 2017. Data and information collected through observation, documents collection, interview of Bogor Educational office, Bogor Education Committee, Task Force of Student Brawling, schools staff, teachers, and student that include on brawling. The conclusion is that the most frequent student brawling occurs in Bogor city was triggered by the enemy perception of the student toward another school student, even toward other school groups. This perception could trigger the conflict whenever and wherever they met without policeman or teacher supervision. This enemy perception had raised a long time, as the olden generation inherit it to their younger generation, and keep maintained. Therefore, the solution to stopping student brawling in Bogor city is to eliminate the perception of the enemy towards other schools or other school groups.